Design Matters : CBNRM and Democratic Innovation - Smith, Graham (World Bank, Washington, DC, 2019)
Community-based natural resource management (CBRNM) aims to realize sustainable management of resources and improvements in livelihood. A central focus is the empowerment of indigenous and local communities through customary or devolved rights to common pool resources. Less attention is given to the extent to which inclusive forms of governance are realized in CBNRM. Democratic innovations are institutions designed explicitly to increase and deepen citizen participation in political decision-making. A number of exemplary cases around the world provide evidence that it is possible to empower citizens in ways that are inclusive and achieve desirable outcomes such as redistribution, recognition of marginalized groups, and improved livelihoods. By clarifying elements of the design of democratic innovations - in particular goods, tasks, mechanisms, and co-design - it is possible to understand how effective forms of participatory governance can be crafted. With careful attention to the endogenous practices of indigenous and local communities and the governance structures imposed by public authorities, CBNRM practitioners can draw on these elements of democratic design to craft forms of inclusive participatory governance that promote sustainable management of resources and improve livelihoods. A program of collaboration between CBNRM and democratic innovations practitioners will contribute to improvements amongst both communities of practice and the communities they serve.